2012
DOI: 10.1007/s10620-012-2486-8
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Spontaneous HCV Clearance in HIV Infected and Uninfected Women

Abstract: Background/Aims Among individuals without human immunodeficiency virus (HIV), African Americans have lower spontaneous clearance of hepatitis C virus (HCV) than Caucasians, and women have higher clearance than men. Few studies report racial/ethnic differences in acute HCV in HIV infected, or Hispanic women. We examined racial/ethnic differences in spontaneous HCV clearance in a population of HCV mono- and co-infected women. Methods We conducted a cross sectional study of HCV seropositive women (897 HIV infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…The development of liver fibrosis can take years, and prolonged THC use may be required to change rates of liver fibrosis. Similar to other published studies, we found that presence of baseline fibrosis, entry CD4 count and HCV RNA level, and ongoing alcohol consumption were predictive of significant fibrosis in WIHS follow-up [27,28], whereas African American race was found to be protective [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…The development of liver fibrosis can take years, and prolonged THC use may be required to change rates of liver fibrosis. Similar to other published studies, we found that presence of baseline fibrosis, entry CD4 count and HCV RNA level, and ongoing alcohol consumption were predictive of significant fibrosis in WIHS follow-up [27,28], whereas African American race was found to be protective [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…Forty‐three studies were included in the analysis of demographic, clinical and behavioural factors associated with HCV clearance, representing a total of 20 110 individuals. The following groups were significantly less likely than others to spontaneously clear HCV: males (OR = 0.68, 95% CI: 0.59‐0.81), those with asymptomatic infection (OR = 0.38, 95% CI: 0.27‐0.55), black race (OR = 0.38, 95% CI: 0.20‐0.75), older adults (age ≥45 years, OR = 0.52, 95% CI: 0.64‐0.97), those with HIV co‐infection (OR = 0.50, 95% CI: 0.37‐0.67), those without hepatitis B co‐infection (OR = 0.24, 95% CI: 0.19‐0.32), patients with nongenotype 1 infection (OR = 0.63, 95% CI: 0.45‐0.89), nonaboriginal groups (OR = 0.47, 95% CI: 0.36‐0.62), and those with excess alcohol use (OR = 0.67, 95% CI: 0.47‐0.95) and those with a history of injecting drug use (OR = 0.59, 95% CI: 0.37‐0.93).…”
Section: Resultsmentioning
confidence: 99%
“…State-level differences in incarceration rates by race might also track with local differences in HCV prevalence. Acute HCV clearance has been hypothesized to be lower in African Americans compared to Hispanic and white counterparts [ 33 35 ]. This is supported by viral clearance being lower in genotype 1 infections, which occur more frequently in African Americans.…”
Section: Discussionmentioning
confidence: 99%